A representação e análise temporal da distribuição da cultura canavieira em substituição as áreas de pastagem e vegetação arbórea no município de Ipeúna-SP de 1995 a 2015 - Gonçalves, Matheus Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
O presente trabalho teve por centralidade estudar a atuação da cultura canavieira no município de Ipeúna localizado na porção nordeste do estado de São Paulo, inserido no quadrilátero açucareiro paulista, área de demasiado adensamento da produção sucroalcooleira. Com isso a pesquisa se organizara primordialmente na análise temporal da atuação desta cultura, evidenciando sua distribuição espacial no território municipal em períodos de 5 (cinco) anos (1995, 2000, 2005, 2010, 2015), por meio do Sistema de Informações Geográficas (SIG) e utilizando como processamento digital em imagens orbitais da série LANDSAT, possibilitando averiguar sua área de abrangência em relação as áreas de pastagem e vegetação arbórea. A partir do mapeamento torna-se possível a representação e distribuição da cultura canavieira em substituição aos elementos analisados ao longo do período de análise. Observando a organização do campo e sua interação no município de Ipeúna, a fim de promover uma gestão e organização equilibrada no campo.

The present work aimed to study the role of sugarcane culture in the municipality of Ipeúna located in the northeastern portion of the state of São Paulo, inserted in the sugarcane quadrilateral São Paulo, an area of too heavy sugarcane production. Thus the research was organized primarily in the temporal analysis of the performance of this culture, showing its spatial distribution in the municipal territory in periods of 5 (five) years (1995, 2000, 2005, 2010, 2015), through the Geographic Information System ( GIS) and using as digital processing in orbital images of the LANDSAT series, making it possible to ascertain its coverage area in relation to pasture areas and tree vegetation. From the mapping becomes possible the representation and distribution of the sugarcane crop in substitution to the elements analyzed during the analysis period. Observing the organization of the field and its interaction in the municipality of Ipeúna, in order to promote a balanced management and organization in the field.
The representation and temporal analysis of the distribution of sugarcane culture replacing the areas of pasture and arboreal vegetation in the municipality of Ipeúna-SP from 1995 to 2015
Keywords: Cana-de-açúcar; SIG; Rural; Sugar cane; GIS